2016
DOI: 10.1002/adma.201604983
|View full text |Cite
|
Sign up to set email alerts
|

A Generalizable Strategy for the 3D Bioprinting of Hydrogels from Nonviscous Photo‐crosslinkable Inks

Abstract: An in situ crosslinking strategy is used for 3D bioprinting of nonviscous photo-crosslinkable hydrogels. This method can be generalized to various photo-crosslinkable formulations, maintaining high embedded cell viability and tunable cell behavior. Heterogeneous and hollow filaments can be printed using this strategy, allowing fabrication of complex engineered cell-laden constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
461
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 446 publications
(469 citation statements)
references
References 30 publications
0
461
0
Order By: Relevance
“…Following hydrogel loading into syringes, syringes were placed into an Instron 5848 mechanical testing machine using a 50 N load cell to assess required forces to maintain a flow rate of 2 mL/h under compression. Printing was performed using a stepper motor‐driven piston‐based nozzle suitable for extrusion on a commercial 3D Fused Deposition Modeling printer (Revolution XL, Quintessential Universal Building Device) as previously described . Standard software was used to generate G‐code (Slic3r) based on 3D computer‐aided design (CAD) models (AutoCAD) and to control hardware (Repetier).…”
Section: Methodsmentioning
confidence: 99%
“…Following hydrogel loading into syringes, syringes were placed into an Instron 5848 mechanical testing machine using a 50 N load cell to assess required forces to maintain a flow rate of 2 mL/h under compression. Printing was performed using a stepper motor‐driven piston‐based nozzle suitable for extrusion on a commercial 3D Fused Deposition Modeling printer (Revolution XL, Quintessential Universal Building Device) as previously described . Standard software was used to generate G‐code (Slic3r) based on 3D computer‐aided design (CAD) models (AutoCAD) and to control hardware (Repetier).…”
Section: Methodsmentioning
confidence: 99%
“…To date, a variety of photo-crosslinkable hydrogels have been developed with tunable mechanical and chemical properties (e.g.,swelling rate, degradability and mechanical strength) for various biomedical applications [14]. As aforementioned, compared with other stimuli (e.g.,pH or temperature), light stimulus is an interesting option as it can be easily controlled to precise locations at defined times and produce hydrogel structures with desirable properties [15].…”
Section: Photosensitive System For the Synthesis Of Photo-crosslinkabmentioning
confidence: 99%
“…SMP-based 4D printing offers structural modification and recovery in response to temperature, which are established through complex functionalities of multiple or reversible shape switching, and such printing may provide inspiration for the molecular architecture of shape memory hydrogels (SMHs). [25][26][27][28][29] The first hydrogel-based bilayer actuation system composed of pNIPAM and acrylamide, obtained through conventional mold techniques, was demonstrated by Hu et al; [25] after that, a range of self-assembled, origami-inspired structures were reported, [27,[30][31][32][33][34][35][36][37][38] but only a few works successfully realized 4D printing with hydrogels. [22] Therefore, mechanically active, self-shaping hydrogels that undergo desired, programmable 3D shape transformations and execute mechanical tasks as soft robots under an external trigger have recently attracted growing interest.…”
mentioning
confidence: 99%